2023
DOI: 10.1111/jac.12637
|View full text |Cite
|
Sign up to set email alerts
|

NDVI and grain fill duration are important to be considered in breeding for terminal heat stress tolerance in wheat

Abstract: Terminal heat stress is a major constraint for taking a profitable crop of wheat by small and marginal farmers in the Indo‐Gangetic Plains of south Asia. Hence, breeders remain in constant search for heat‐tolerant genotypes. This study was done with the purpose to find out high‐yielding wheat genotypes that perform stably under terminal heat stress as well as to conclude an easy phenotyping trait for this objective. A cross (HUW 234 × HUW 468) was made using two popular cultivars of the eastern Gangetic Plains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…This suggested that the heat stress had no impact on the overall greenness of the wheat cultivar. Kumar et al, 2023 reported that the NDVI value at the anthesis stage and grain lling stage was crucial for understanding the heat stress tolerance capacity of wheat. NDVI value was not statistically signi cant among the two treatments which implies that the variety of wheat is somewhat resistant to heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the heat stress had no impact on the overall greenness of the wheat cultivar. Kumar et al, 2023 reported that the NDVI value at the anthesis stage and grain lling stage was crucial for understanding the heat stress tolerance capacity of wheat. NDVI value was not statistically signi cant among the two treatments which implies that the variety of wheat is somewhat resistant to heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…The possible use of SEMs to understand physiological causes of genotype by environment or management interaction was explored by Vargas et al (2007), who concluded that the approach can facilitate the understanding of the effects of environmental covariates on yield performances or can be used to generate hypotheses (Valente et al, 2013). Under heat stress, SEM confirmed the role of HDD_A and HDD_GF in controlling NDVI (as NDVI and IT_NDVI), hence plant growth and biomass development, which in turn plays a key pivotal role in influencing of PH, KNS, TKW and finally GY, as recently pointed out by Kumar et al (2023).…”
Section: Discussionmentioning
confidence: 81%